Mac bible - Spivey, Dwight (Bible Ser., 2009)
"This essential guide answers all your questions on using a Macintosh computer, whether you're unpacking your very first Mac after switching from a PC or upgrading from an older Mac. You'll walk through all pre-installed Mac applications, including using Mac OS X, browsing the Web using Safari, downloading music from the iTunes store, troubleshooting Mac-specific problems, organizing photos in iPhoto, organizing calendars in iCal, editing digital video in iMovie, and more."--Resource description page